Os processos cognitivos da aprendizagem matemática por meio de uma didática específica para estudantes surdos - Pinto, Mariê Augusta de Souza (2013)
The present study hunts to do a theoretical analysis of the investigations about the processes of learning of Mathematics contents associated to logical thought and the solving problems of deaf students by Brazilian Signal Language (LIBRAS). In general aspects, it is analyzed how the cognitive processes (reasoning and solving Mathematics problems) are stimulated and how it is developed by under-graduated students during the interactive activity with deaf students. The research is qualitative involving ten (10) deaf students from a specialized school for Deaf Education, in Parintins, Amazonas, by using as provoking didactic instrument the creation and the didactical implementation of a multiplication table entitled “MinhaTabuadaem Libras”which aims to favor and potentializeit as a support for educators to develop other mechanisms that make much more feasible the learning of that student. By those ways pre and pro tests were applied in order to found the objective of the research as well as to prove whether the learning of the student in consideration happens in the same levels of hearing student. The research solves the scientific problem which has as basis: “ How does the learning of Mathematics problems happen associated to logical thought and reasoning of deaf student by LIBRAS?”. The theoretical referent which allowed the made of the theoretical mark to structure the research has the ideas of Sternberg (2010) relating to cognitive processes, language, signs language and others. Also it is important to emphasize the works of Gesser (2009), Chomsky (1975), Laborrit (1994) etc. The use of plays, bingos and other concrete materials were significant as facilitators to learning in special Brazilian Signs Language (LIBRAS) necessary in the process of communication, interaction and the development of non-hearing people.